Impact of absent crowds on technical and physical performances in the Chinese Soccer Super League - Chen, Junjin; Zhai, Shuaishuai; Xi, Zenghui; Li, Peilun; Zhang, Shuolin (Frontiers in Psychology, 2022)
Purpose: Spectators have a significant impact on match performances in soccer, but to what extent crowd support contributes to the technical and physical performances remains unclear. The aim of this study was to 1) investigate the differences in terms of technical and physical performances with and without spectators; 2) identify the key factors differentiating between win and loss when playing with and without the presence of an audience. Methods: Our study examined 794 performance records from 397 matches during the 2019-2020 seasons in the Chinese Soccer Super League. Lasso-logistic regression was utilized to select significant predictors. Using an independent t-test and Mann-Whitney nonparametric test explores the difference between matches with and without spectators. Key factors between win and loss were explored using univariate and multivariate logistic regression analyses. Results: Our study found that cross (P < 0.01, ES = -0.24), shots (P < 0.001, ES = -0.25), and shot accuracy (P < 0.05, ES = -0.18) displayed decreasing trends whereas sprint distances (P < 0.05, ES = 0.16) presented an increasing trend without spectators comparing with the crowd support. Moreover, the above three technical variables were the main factors differentiating between win and loss. Likewise, team and opponent quality remained the important potential factors to affect the match outcome. Conclusion: Match outcome or team performance is determined by a myriad of factors, but there are clear differences in technical and physical performances between matches with and without the presence of an audience. Similarly, our study provides a better explanation for the impact of crowd support on match performances whereby coaches can deploy players and adjust match strategies to ultimate success.